Data security in mobile healthcare - Zajeganović, Marija B.; Vugdelija, Natalija J.; Stefanović, Radiša R.; Kostić, Silva M.; Miljković, Uroš D.; Mach, Georg G. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The digitization of healthcare has gained particular importance in the years since the emergence of COVID-19 and also has become one of the primary goals of the Government of the Republic of Serbia. Telemedicine is a good solution when the patient cannot come to a healthcare facility. Mobile healthcare applications are already widely used, but in both fields the important challenge is data security. The aim of this paper is to review solutions for data security in mobile healthcare from the technical side and possible challenges in the process of digitization of the healthcare system in Serbia. Methods: This review is based on current papers in this area, on the available relevant literature and the authors’ many years of experience in this field. Experiences in the process of digitization of healthcare in Serbia are based on available articles and regulations. Finally, possible challenges are presented from the authors’ perspective based on everything presented in the field of data security in mobile healthcare. Results: The analysis of the papers reviewed from the point of view of data security showed that users are often ready to sacrifice their privacy for the sake of convenience provided by mobile applications. Conclusion: Based on the review of the papers and clear data security requirements that include the presented safeguards, one of the main tasks of the entire community is to raise awareness of information security and awareness of the need for cyber hygiene of each individual, which is the basis for the safe use of e-health services.